2007
DOI: 10.1016/j.canlet.2007.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of arsenic-binding proteins in human breast cancer cells

Abstract: As a cancer chemotherapeutic drug, arsenic acts on numerous intracellular signal transduction pathways in cancer cells. However, its mechanism of actions is still not fully understood. Previous studies suggest that arsenic reacts with closely spaced cysteine (Cys) residues of proteins with high Cys content and accessible sulfhydryl (SH) groups. In this study, human breast cancer cell line MCF-7 was examined as a cellular model to explore arsenic-binding proteins and the mechanism of binding. An arsenic-biotin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 55 publications
4
69
1
1
Order By: Relevance
“…In particular, As(III) was shown to directly bind to b-tubulin isolated from a human breast cancer cell line and structural modeling suggested the amino acid residue Cys12 is key to such a physical interaction (Zhang et al 2007). This model of arsenic action would be consistent with most of Table S3.…”
Section: Resultssupporting
confidence: 68%
“…In particular, As(III) was shown to directly bind to b-tubulin isolated from a human breast cancer cell line and structural modeling suggested the amino acid residue Cys12 is key to such a physical interaction (Zhang et al 2007). This model of arsenic action would be consistent with most of Table S3.…”
Section: Resultssupporting
confidence: 68%
“…Arsenic bound to five of the key enzymes involved in glycolysis, i.e., hexokinase, aldolase, triose phosphate isomerase, GAPDH, and phosphoglycerate kinase. A previous study (10) identified another set of four enzymes involved in glycolysis as targets of arsenic, i.e., PKM2, enolase, pyruvate carboxylase, and L-lactate dehydrogenase B chain. Thus it is clear that the majority of the enzymes in the glycolysis pathway can be targeted directly or indirectly by arsenic.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Briefly, the arsenic-biotin conjugate, biotinylated p-aminophenylarsenoxide (Biotin-As) (10), was incubated with the human proteome microarray, and proteins with arsenic-binding capacity were identified by adding Cy3-conjugated streptavidin (Cy3-SA). To avoid false-positive detections, we compared this sample with another in which Biotin-As was omitted from the reaction and free biotin was included instead and identified as arsenic-binding candidate proteins those exhibiting markedly greater signals in the former reaction.…”
Section: Global Profiling Of Arsenic-binding Proteins Using a Human Pmentioning
confidence: 99%
See 2 more Smart Citations